A new imaginary: contributions of women in America - Pérez Díaz de Arcaya, Edurne (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2018)
The arrival to Berlin of Nazis SS troopes in 1933 caused the exodus of European artists and architects. They flight together with their wifes escaping from an imminent war. Many of them found the promise of a new opportunity in North Carolina: the Black Mountain College. An experimental school opened its doors in the middle of an economic recession, with the goal of teaching to think. Prominent European figures arrived to North Carolina with the hope of continuing their projects. Their wifes and female colleagues turned the nothing which they find to a big opportunity. With them other women joined Black Mountain College experience and created a new generation hidden for the men’s practice. Women, used to work with practically nothing, found there the framework for the beginning of a new way of thinking. The classrooms were opened to new fields like mathematics or geometry turning the European ateliers into experimental laboratories. Anni Albers showed these women how to weave the nothing as a new matter. With her, Ruth Asawa, Dorotea Rokburne and Anne Tyng built a new way of thinking detached, as they, of any material. This hidden generation didn´t provide built samples, but a new imaginary for another architecture.
Keywords: Black Mountain College; women; nothing; laboratories; idea; hidden